Антология выдающихся достижений в науке и технике. Часть 29: Первооткрыватели тайн глобальных природных световых явлений - Баранов, М.И. (Електротехніка і електромеханіка, 2015)
Приведен краткий научно-исторический очерк про раскрытие отечественными и зарубежными ученымипервопроходцами электрофизических и электрохимических тайн ряда природных световых явлений, носящих для
человечества глобальный планетарный характер и сопровождающих протекание в околоземном атмосферном пространстве полярного сияния, радуги и фотосинтеза. Наведено короткий науково-історичний нарис про розкриття вітчизняними і зарубіжними вченимипершопроходцями електрофізичних і електрохімічних таємниць ряду природних світлових явищ, що носять для людства глобальний планетарний характер і які супроводжують протікання в навколоземному атмосферному просторі
полярного сяйва, веселки і фотосинтезу. Purpose. Scientifically-historical description of features of
opening by scientists-discoverers of the world of electrophysics
and electrochemical secrets of such natural light phenomena as
Aurora Borealis, rainbow and photosynthesis, carrying global
planetary character for the habitants of planet Earth. Methodology. Scientific approaches at treatment and systematization of
physical knowledges about «solar wind» and sun radiation,
causing flowing in the atmosphere of Earth of the indicated light
phenomena. Methods of historical method at research of progressive development in the world of basic scientific knowledges
about the examined natural light phenomena. Results. Basic
information, touching forming of scientific bases of electrophysics and electrochemical processes, flows at a display in the
earthly atmosphere of aurora north (south) polaris, primary
(second) rainbow and photosynthesis domestic and foreign scientists in the leaves of higher (lower) plants, is resulted. Originality. First in area of history of scientific and technological
bases of electrophysics and electrochemical processes, characteristic for aurora polaris, rainbow and photosynthesis in an
earthly magnetic sphere and air atmosphere are presented in the
short systematized form and historical development. Practical
value. Scientific popularization of electrophysics and electrochemical knowledges and distinguished scientific achievements
in area of such global for a planet Earth of the natural atmospheric light phenomena as aurora Borealis, rainbow and photosynthesis.